Non-achalasia esophageal motility disorders: Role of per-oral endoscopic myotomy - Zaheer Nabi; Duvuur Nageshwar Reddy (Society of Gastrointestinal Intervention, 2020)
Major disorders of esophageal peristalsis other than achalasia include Jackhammer esophagus (JHE), distal esophageal spasm (DES), and esophagogastric junction outflow obstruction (EGJOO). These disorders are rare, distinct from achalasia and characterized by high resolution manometry. Unlike achalasia, the treatment strategies are not well defined in these disorders. Therapies directed at lower esophageal sphincter may be inadequate in JHE and DES as a variable length of esophageal body is also involved in symptom generation. On the other hand, EGJOO is a more heterogenous group and the decision for endoscopic treatment is based on comprehensive evaluation of the underlying etiology. A subset of patients with EGJOO without significant stasis may improve on conservative treatment. Per-oral endoscopic myotomy (POEM) is a newer endoscopic treatment modality that has established its role in the management of achalasia. Limited studies suggest the efficacy of POEM in non-achalasia esophageal motility disorders as well. The ability to perform long esophageal myotomies with POEM makes it an attractive management tool for these patients.